The librarian and the bureaucratic administration at school: an approach of the Political-Pedagogical Project and the professional performance - Camillo, Everton da Silva [UNESP]; Castro Filho, Claudio Marcondes de (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2019)
It is assumed as a presupposition for this study that school librarians develop a merely technical performance in schools possibly corroborated by the adhesion of the bureaucratic model of administration. This bias, however, conflicts with the acknowledgment of the technical-intellectual ambivalence of the library professional, given its various facets and professional skills that are fundamental to the school scene of the twenty-first century. In this sense, this study aimed to present the professional performance of school librarians and their experiences with the Political-Pedagogical Project of the schools where they work, considering the context of the school's bureaucratic administration. Methodologically, it was carried out a study of exploratory, quantitative and descriptive approaches. We collected the data in four Facebook thematic groups from the application of a virtual questionnaire in the month of June 2018. As a result, we obtained that: (1) there is a narrow organizational vision on the part of the group of schools, because it creates the impression that this same group makes the possibility of horizontally and concretely interdisciplinary work impossible in the school and (2) there are institutional centrality and bureaucracy that interfere in the reach and possibility of contribution of the other professionals of the school for the construction and/or reformulation of the Political-Pedagogical Project, when the school librarian joins.
Keywords: School library; Political Pedagogical Project; Bureaucratic pedagogy; Professional performance; School librarian